The price system and resource allocation - Leftwich, Richard H.; Holt, Rinehart (Chicago : Dryden Press, 1970)
This book builds on the concept of welfare in the sense of Pareto optimality. Also the theory of consumer choice
Includes bibliographical references and indexes.
mf 24/01/2019
Loans
Keywords: Prices; Microeconomics